P Factors of 3P Theory in Gender Conflict - Yadam Ram Kumar (Journal of Sociological Research, 2024)
The research is original and based on analysis of the P factors of 3P Theory in the context of interpersonal conflict in society. The research studies a person in the context of gender and investigates the Gender Conflict with P factors, i.e., P1 (Personal), P2 (People or Society), and P3 (Power) factors of the 3P Theory. P3, power factor, which is further subdivided into E1 (education), E2 (economics), and E3 (energy). Inter-gender and intra-gender relations are defined universally and the conflict analyzed. The objective of research is to understand the factors responsible for conflict between two genders, especially male and female, with the aim of finding a sustainable solution to curb gender-related violence, especially violence against women. Gender conflict is a primary victim of gender conflict in the world. The conflict in relations between two individuals or genders is explained through 3P Theory formulas.